EFFECT OF WATER SPINACH (Ipomoea aquatica) CONSUMPTION ON HEMOGLOBIN LEVELS IN PREGNANT WOMEN - Dessy Lutfiasari; Alfika Awatiszahro (Universitas STRADA Indonesia, 2025)
Anemia is a common condition among pregnant women, primarily caused by iron deficiency, and may lead to complications during pregnancy and childbirth. The 2023 Indonesian Health Survey (SKI) reported that 27.7% of pregnant women still experience anemia. Nutritional interventions using vegetables rich in iron and vitamin C, such as water spinach (Ipomoea aquatica), may provide an alternative strategy to improve hemoglobin levels. This study aimed to determine the effect of water spinach consumption on hemoglobin levels in pregnant women. This research used A pre-experimental design with a one-group pretest–posttest approach. The research sample consisted of 30 pregnant women. Hemoglobin levels were measured using a hemoglobin testing device, and observations were recorded on structured sheets.